2017
DOI: 10.3389/fcimb.2017.00495
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Lipoprotein Z-Specific IgA in Tuberculosis and Latent Tuberculosis Infection

Abstract: Tuberculosis (TB) remains one of the most severe infectious diseases. It is still of paramount importance to establish more accurate, rapid, and efficient diagnostic methods. Since infection with Mycobacterium tuberculosis (M. tb) is largely mediated through the respiratory tract, IgA responses against mycobacterial proteins are worthy of investigation for their potential clinical utility. In this study, the IgA response targeting lipoprotein Z (LppZ) was determined by using a homemade ELISA with plasma of TB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 44 publications
3
15
0
Order By: Relevance
“…Another previous study found that anaerobic bacteria such as Fusobacterium, treponema, Tannerella and Prevotella rapidly increased in mature plaque over 4 days, and they were associated with gingivitis and periodontitis [21]. Moreover, periodontopathic plaque shows higher richness compared to healthy plaque, and this increases with the FIGURE 3 Relative abundance of the phylum-level community (A) and the genus-level community (B) identified in non-RF and RF plaque samples; genera marked with an asterisk (*) exhibited significant differences in relative abundance (Wilcoxon rank-sum test, P < .05) FIGURE 4 Linear discriminant analysis (LDA) effect size (LEfSe) analysis of bacterial taxa present in RF plaque (red bar) and non-RF plaque (gray bar) at the genus level periopathogenicity [16,22,23]. It is therefore reasonable that the red fluorescence emitted by dental plaque indicates increased maturity and pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Another previous study found that anaerobic bacteria such as Fusobacterium, treponema, Tannerella and Prevotella rapidly increased in mature plaque over 4 days, and they were associated with gingivitis and periodontitis [21]. Moreover, periodontopathic plaque shows higher richness compared to healthy plaque, and this increases with the FIGURE 3 Relative abundance of the phylum-level community (A) and the genus-level community (B) identified in non-RF and RF plaque samples; genera marked with an asterisk (*) exhibited significant differences in relative abundance (Wilcoxon rank-sum test, P < .05) FIGURE 4 Linear discriminant analysis (LDA) effect size (LEfSe) analysis of bacterial taxa present in RF plaque (red bar) and non-RF plaque (gray bar) at the genus level periopathogenicity [16,22,23]. It is therefore reasonable that the red fluorescence emitted by dental plaque indicates increased maturity and pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work has also reported that LppZ-specific IgA levels in TB patients and latent TB infection (LTBI) individuals were dramatically higher than that in healthy controls (HCs). LppZ-specific IgA level decreased substantially along with the anti-TB treatment (Xiao et al, 2017). What’s more, its potential as a new TB vaccine candidate antigen was evaluated with enhanced immune protection against M.tb challenge in mouse models (under revision manuscript).…”
Section: Introductionmentioning
confidence: 99%
“…However, our study was not designed to speci cally address the effect of alcohol in humoral response of TB patients, more studies are needed to elucidate these serological ndings. Moreover, lower positive IgA PPE 59 frequency in IT patients may be related to treatment, as recently described for LppZ IgA low response after 2 months of anti-TB treatment [38], however, our study was not designed to follow up the treated patients. No other demographic or clinical characteristic was associated with Ab positivity among Italian/immigrants, especially for IgG, which is mainly due to the low number of individuals who were positive for the test.…”
Section: Discussionmentioning
confidence: 87%